Human rights quarterly - Johns Hopkins University Press (Johns Hopkins University Press, 1981)
7 parts: from conquest to constitutions: retrieving a latin American tradition of the idea of Human Rights; The UN as a Human rights violator? some reflections on the United Nations Changing Human Rights Responsibilities;...